2017
DOI: 10.1016/j.commatsci.2016.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Metastable phases, phase transformation and properties of AlAs based on first-principle study

Abstract: By utilizing an evolutionary methodology on crystal structure search, we propose three new metastable phases for aluminum arsenide (AlAs) as follows: (1) a P6 4 22 symmetric structure 3 (hP6-AlAs), (2) a C222 symmetric structure (oC12-AlAs), and (3) a I3d symmetric structure 4 (cI24-AlAs). By controlling the unloading pressure rate, oC12-, hP6-, and cI24-AlAs may be acquired through quenching NiAs-AlAs. The elastic constants and phonon dispersion spectra are calculated to certify the mechanical and dynamic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…Recently,m ore and more researchers have begun to study the polymorphs of the XN compounds (X = Al, Ga, In). [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Yang et al [6] investigated the structural, elastic,thermodynamic, electronic, and opticalp roperties of four novel compounds: Pmn2 1 -AlN, Pbam-AlN, Pbca-AlN, and Cmcm-AlN. They found that the AlN in the Cmcm phase has ab etter plasticity and also has al arger elastic anisotropyi nY oung's modulus than Pmn2 1 -AlN, Pbam-AlN, and Pbca-AlN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently,m ore and more researchers have begun to study the polymorphs of the XN compounds (X = Al, Ga, In). [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Yang et al [6] investigated the structural, elastic,thermodynamic, electronic, and opticalp roperties of four novel compounds: Pmn2 1 -AlN, Pbam-AlN, Pbca-AlN, and Cmcm-AlN. They found that the AlN in the Cmcm phase has ab etter plasticity and also has al arger elastic anisotropyi nY oung's modulus than Pmn2 1 -AlN, Pbam-AlN, and Pbca-AlN.…”
Section: Introductionmentioning
confidence: 99%
“…They found that their hardness and Debye temperaturesb oth decrease with the X( X = N, P, As) atomic number,t hat is to say,f or wurtzite andz incblende, the hardnessand Debyet emperature are in the order of AlN > AlP > AlAs. Aq uasi-harmonic approximation was used to systematically evaluate the temperature dependence of thermodynamic properties for AlX (X = N, P, As) compounds.B yu tilizing an evolutionary methodology in ac rystal structure search, Liu et al [10] proposed three new metastable phases for AlAs, namely, hP6-AlAs, oC12-AlAs, and cI24-AlAs, the space groups being P6 4 22, C222, and I4 3d,r espectively.F rom electronic band-structure calculations, cI24-AlAs is ad irect semiconductor materialw ith ag ap value of 1.76 eV,w hereas oC12-and hP6-AlAs are indirect semiconductor materials with band gaps of 0.47 eV and 1.36 eV,respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We performed global minimization of FeS 2 (at T = 0 K) by merging ab initio total energy calculations and the calypso technique on structural predictions, as implemented in the CALYPSO code [16][17][18]. The CALYPSO method has been successful to correctly predict HP structures for various systems [19][20][21][22][23]. The underlying ab initio electronic structure calculations and geometry relaxations were performed in the framework of density functional theory (DFT) using the Perdew−Burke−Ernzerhof (PBE) exchange−correlation functional [24] within GGA as implemented in the Vienna ab initio simulation package (VASP) code [25].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Therefore, in the application of semiconductors, compatibility means are often used to make the two compatible and utilize their respective advantages. Because of this, more and more attention has been paid to research on new structures and the physical properties of the compounds [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%